Managing Alcohol Use Disorder in Primary Health Care - Anderson, Peter (Curr Psychiatry Rep, 2017)
PURPOSE OF REVIEW: The aim of this study is to summarise the current literature on both the impact and the implementation of primary health care-based screening and advice programmes to reduce heavy drinking, as an evidence-based component of managing alcohol use disorder in primary health care. RECENT FINDINGS: Systematic reviews of reviews find conclusive evidence for the impact of primary health care delivered screening and brief advice programmes in reducing heavy drinking. The content, length of advice and which profession delivers the advice seems less important than the actual encounter between provider and patient. Despite the global burden of disease due to heavy drinking and the evidence that this can be reduced by screening and brief advice programmes delivered in primary health care, such programmes remain poorly implemented. Were such programmes widely implemented, there would be substantial health and productivity gains. Systematic reviews and international studies indicate that improved implementation requires tailoring of training and programme content to match the needs of providers, training and ongoing support and embedding of programmes within local community support, championed by local leaders. SUMMARY: The next stage of implementation and scale-up of evidence-based screening and brief advice programmes should take place embedded within supportive local community action, with appropriate research to demonstrate impact.